Exploring a South African solution to an international concern over auditor independence: The South African audit profession's opinions with regard to mandatory audit firm rotation - Harber, Michael (Department of Finance and Tax, 2017)
The provision of assurance services, most notably the audit function, is an activity of public protection that requires a high degree of independence between the auditor and the audit client to ensure audit quality is achieved. Internationally, especially in the European Union, there is a legislated move towards mandatory audit firm rotation (MAFR) to ensure auditor independence. South Africa is currently faced with the decision of whether to change legislation and follow suit. Using a qualitative and descriptive methodology, through the use of semi-structured and open interviews with experienced South African audit partners, the direct and indirect effects of mandatory firm rotation on the audit profession was explored. This study will therefore present the opinions of the regulator and a small group of experienced audit partners, most being regional or national managing partners, from audit firms that perform public interest entity audits. Of particular interest will be the opinions of the respondents around (1) the state of independence in South Africa, (2) whether mandatory audit firm rotation will increase audit quality, (3) whether there are better alternatives to mandatory audit firm rotation, and (4) what the perceived direct and indirect effects of mandatory rotation will be within the South African legal and regulatory context. A particular emphasis is also placed on the argument from the national audit regulator that mandatory audit firm rotation, in addition to strengthening independence, will also reduce market concentration (promote competition) in the South African audit industry, as well as promote black economic transformation. The results show significant disagreement by the audit practitioners against the arguments in favour of mandatory audit firm rotation, with most claiming that it will not achieve an increase in audit quality and will produce many unintended consequences that will in their opinion actually reduce audit quality. There is a significant amount of agreement amongst the audit partners on the key issues and no partner interviewed is fully in favour of changing legislation to require MAFR. A number of alternative means for improving audit quality are suggested, which in the opinion of many of the partners, will be less damaging to audit quality and the audit profession.